Einige Fragen der Aktionsart- und Aspektfunktion im Sprachvergleich - Kotin, Michail L. (Studia Germanica Posnaniensia, 2018)
The contribution deals with selected questions of the interaction between the so called “lexical aspect” (the opposition between telicity and atelicity) and the grammatical aspect (or so called “viewpoint”- aspect, i.e. the opposition between perfectivity and imperfectivity) in the languages with and without the overtly encoded aspect. The striking point of the analysis is the “complexive” meaning of aspectual forms and constructions involving lexical atelicity by indicating durativity or iterativity, on the one hand, and grammatical perfectivity by indicating the complexive perspective of the verbal action on the other. This type of aspectuality was a special feature of verbal systems with the aorist category. My claim is, thus, that the contemporary English has a special grammatical form of the “complexive aorist”, i.e. the form of Present Perfect Progressive. The Slavic languages encode this function by using the – unmarked – imperfective forms of the verbs, whereas German uses special means of encoding the very same function on the whole-clause level, such as adverbials or definite vs. indefinite or zero article.